Adventures in the Big Thicket - Gire, Ken.; Miles, Elizabeth J. (Pomona, Calif. : Focus on the Family Pub., 1990)
Follows the adventures of a group of small animals living in a bayou in East Texas. Each adventure concludes with a Bible verse.
Keywords: Animals -- Fiction; Bayous -- Fiction; Christian life -- Fiction; Big Thicket (Tex.) -- Fiction